Power Laws in Adsorption and the Characterization of Heterogeneous Substrates - F. Bulnes; A.J. Ramirez-Pastor; G. Zgrablich (Adsorption Science & Technology)
The adsorption of particles with repulsive nearest-neighbour interactions was studied through Monte Carlo simulation on bivariate surfaces characterized by patches of weak and strong adsorbing sites of size l. Patches were either arranged in a deterministic chessboard structure or in a random way. Quantities were identified which scale obeying power laws as a function of the scale length l. The consequences of these findings were discussed for the determination of the energetic topography of the surface from adsorption measurements.